An empirical model of social and healthcare educators' continuing professional development in Finland. (17th June 2021) - Koskimäki, Minna; Mikkonen, Kristina; Kääriäinen, Maria; Lähteenmäki, Marja‐Leena; Kaunonen, Marja; Salminen, Leena; Koivula, Meeri
Abstract: The objective of this work was to develop and test an empirical model of social and healthcare educators' continuing professional development. A cross‐sectional survey study design was adopted, and a total of 422 part‐time and full‐time social and healthcare educators from 28 universities of applied sciences and vocational schools in different regions of Finland participated. Data were collected from October to December in 2018. The participants taught in the fields of healthcare, social services, and rehabilitation. The questionnaire included the EduProDe scale and background questions. Confirmatory factor analysis and structural equation modelling were used to develop the model, and its quality was assessed by computing goodness of fit indexes. The main finding was that when educators understand the benefits of continuing professional development, they will recognise their developmental needs and proactively seek support from their superiors. The results obtained provide insight into the preconditions for professional development and offer guidance for the design of future shared development programmes or activities for social and healthcare educators.